Deliberative Democracy: The Case of Slovenia - Haček, Miro; Kukovič, Simona (Political Preferences, 2020)
In Europe and across the world, many countries are turning to deliberative democracy to reform their constitutions, and in many others this question is high on the political agenda. Such transformation also shuffles quite radically the role of the citizenry regarding constitutional changes. Traditionally such changes are the sole responsibility of elected officials in collaboration with experts. With the deliberative turn, many more actors may be involved in the designing of constitutions, from citizens both individually and collectively in the forms of informal associations to various civil society organisations. The main aim of this paper is to analyse potential of deliberative democracy in Slovenian national setting, therefore authors are analysing a) framework of constitution making dynamics and b) most successful deliberative democratic tools and opportunities developed so far on both national and sub-national levels of the Slovenian government. As deliberative democracy is well known political phenomenon, we will start not by yet another theoretical pandemonium, but with less-known Slovenian contribution to the global development of deliberative model.